LANTANG PANGNGAN SEBAGAI PEREKAT PERSAHABATAN (SUATU TINJUAN DALAM PERSPEKTIF TEOLOGI SOSIAL) - Norpi Norpi; Marselina Mangiri (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Social theology is an understanding of human involvement in the social problems of society. It does not only talk about vertical matters (divine matters) but covers horizontal matters (human relation with humans) such as the value of friendship contained in the making of lantang pangngan(betel hut) in Toraja. Lantang pangngan is a symbol of people who mate mate malolle (die young) in which there is a value of intimacy, namely the expression of the hearts of friends that the grief felt by the family is a shared grief. The meaning of friendship is the existence of a relationship or alieance between individuals who have common interest in which there is a mutual agreement. Thus it can be understood that friendship is an intimate relationship that is sustainable where there is mutual love both in joy and sorrow. This research use descriptive qualitative research methods throught interviews wits tominaa. The benefits of the research found a social theological reflection of the making lantang pangngan the reflection is in the form of fellowship. Where lantang pangngan is the glue of friendship. It can be concluded that lantang pangngan is not just an ordinary tradition but contains the meaning of intimate friendship in joy and srrow.